The Controversy of Interfaith Marriages (A Review of The Effectiveness of Supreme Court Circular Letter Number 2 of 2023 - Martua Marpaung, Rohendi Sahat; Catharina Dewi Wulansari (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Marriages are often problematic, including for couples of the same religion. The problem becomes increasingly complex for those who enter into interfaith marriages. However, the reality of interfaith marriage is a social reality that cannot be avoided. The social and relational nature of humans and the need to meet other people make the potential for interfaith marriages even higher. Humans will increasingly find differences when relating to others who are diverse both in tradition, culture, thought and religion. Catholic teachings and the Code of Canon Law do not require interfaith marriages because it would bring danger to the faith of Catholics. However, the Catholic religion cannot turn away from the social reality where it is not uncommon to find husbands or wives of different religions. Therefore, the Catholic Religion must still consider pastorally interfaith marriages as regulated in Canon 1125 and 1126. In accordance with the provisions of Article 2 paragraph (1) of Law no. 1 of 1974 concerning Marriage states that a valid marriage is a marriage that takes place according to the laws of each religion. A valid marriage must be registered according to the applicable laws and regulations (Article 2 paragraph (2) of the Marriage Law). According to SEMA No. 2 of 2023 concerning Instructions for Judges in Hearing Cases of Applications for Registration of Marriages Between People of Different Religions and Beliefs in number 2 it is stated that the court does not grant requests for registration of marriages between people of different religions. So, if according to one of the religions in Indonesia an interfaith marriage is legal according to the relevant religious law, the court should not refuse to register the marriage at the Population and Civil Registry Service. This research will be carried out using sociological juridical methods using quantitative reasoning.